The relationships between toe strength and balance ability, floating toes, and judo competitiveness in university female judo athletes - Suzuki, K.; Matsui, T.; Kubota, H. (Association for the Scientific Studies on Judo, Kodokan, 2021)
The present study aimed to examine the relationships between toe strength and balance ability, toe strength and floating toes, and toe strength and judo competitiveness for university female judo athletes. Toe strength was measured, balance ability was evaluated, and floating fingers were judged for 34 female athletes (age, 20.1 ± 1.1 years; height, 159.3 ± 6.2 cm; weight, 62.9 ± 12.2 kg; and competition years, 13.8 ± 2.2) in the university judo club. As results, there were no significant relationships between the toe strength and balance ability, the toe strength and floating toes, the toe strength and judo competitiveness. Thus, the relationships between the toe strength and balance ability, the toe strength and floating toes, the toe strength and judo competitiveness were clarified to be low in university female judo players.